2006
DOI: 10.1155/2006/469132
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Phonological Memory Following Transcranial Magnetic Stimulation (TMS)

Abstract: Phonologically similar items (mell, rell, gell) are more difficult to remember than dissimilar items (shen, floy, stap), likely because of mutual interference of the items in the phonological store. Low-frequency transcranial magnetic stimulation (TMS), guided by functional magnetic resonance imaging (fMRI) was used to disrupt this phonological confusion by stimulation of the left inferior parietal (LIP) lobule. Subjects received TMS or placebo stimulation while remembering sets of phonologically similar or di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 31 publications
3
25
1
Order By: Relevance
“…Price, Moore, Humphreys, & Wise, 1997) underlie much of the support for the SMG as a major contributor to phonological processing. Similar results documenting the involvement of the SMG in phonological processing using different tasks and stimuli (serial recall with visually presented pseudowords (Kirschen, Davis-Ratner, Jerde, Schraedley-Desmond, & Desmond, 2006), homophone judgments with visually presented words (Stoeckel, Gough, Watkins, & Devlin, 2009), syllable counting with visual and auditorily presented words and, rhyming judgment with visually presented words (Sliwinska, Khadilkar, Campbell-Ratcliffe, Quevenco, & Devlin, 2012)), have been reported in TMS experiments although the type of effect (inhibitory, facilitatory) varied depending on stimulation parameters (rTMS versus single pulse).…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…Price, Moore, Humphreys, & Wise, 1997) underlie much of the support for the SMG as a major contributor to phonological processing. Similar results documenting the involvement of the SMG in phonological processing using different tasks and stimuli (serial recall with visually presented pseudowords (Kirschen, Davis-Ratner, Jerde, Schraedley-Desmond, & Desmond, 2006), homophone judgments with visually presented words (Stoeckel, Gough, Watkins, & Devlin, 2009), syllable counting with visual and auditorily presented words and, rhyming judgment with visually presented words (Sliwinska, Khadilkar, Campbell-Ratcliffe, Quevenco, & Devlin, 2012)), have been reported in TMS experiments although the type of effect (inhibitory, facilitatory) varied depending on stimulation parameters (rTMS versus single pulse).…”
Section: Introductionsupporting
confidence: 77%
“…J. Price, et al, 1997) and verbal working memory (Awh, et al, 1996;Barch & Csernansky, 2007;Jonides, et al, 1998;Kirschen, et al, 2006;Koelsch, et al, 2009;McKenna, et al, 2013;Paulesu, Frith, & Frackowiak, 1993;Paulesu, et al, 1996;Salmon, et al, 1996;Smith & Jonides, 1999;Smith, et al, 1996), while TMS studies have provided evidence regarding the involvement of the left and right SMG during phonological processing Romero, et al, 2006;Stoeckel, et al, 2009), but based on these studies, the possibility that the experimental tasks used also recruited verbal working memory processes cannot be discounted. To gain a better understanding of the role of the left and right SMG in both verbal WM and phonological processing, we conducted two TMS experiments to test hypotheses regarding the contribution of the left and the right SMG to phonological encoding and verbal WM separately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcranial magnetic stimulation (TMS), introduced nearly 20 years ago, offers a promising alternative for cognitive enhancement in healthy individuals (Luber and Lisanby 2014). While most TMS protocols were originally developed for therapeutic purposes in psychiatry and neurology (Hoy and Fitzgerald 2010;McKinley et al 2012), studies on healthy individuals have demonstrated success in facilitating visual spatial attention (Hilgetag et al 2001;Thut et al 2005), visual search (Hodsoll et al 2009), mental rotation (Klimesch et al 2003), analogical reasoning (Boroojerdi et al 2001), phonological recall (Kirschen et al 2006), and abilities in drawing Young et al 2004), and mathematics, calendar calculating and proofreading (Young et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers at Stanford demonstrated enhancement of phonological memory following TMS (Kirschen et al, 2006). Based on the premise that phonologically similar items (i.e., "mell, rell, gell) are more difficult to remember than dissimilar items (i.e., "shen, floy, stap"), Kirschen and colleagues applied low-frequency TMS, guided by functional magnetic resonance imaging (fMRI), to the left inferior parietal (LIP) lobule.…”
Section: Past Researchmentioning
confidence: 99%